Pengaruh Strategi SQ3R dalam Meningkatkan Hasil Belajar Membaca Siswa Kelas III di SD Negeri 1 Teko Kecamatan Pringgabaya - Selviana, Rani; Hadi, Yul Alfian; Hidayati, Baiq Rizki; Sururuddin, Muhammad (Program Studi Pendidikan Masyarakat, 2026)
Abstract: The main problem in this study is the low reading learning outcomes of third-grade students at SD Negeri 1 Teko, Pringgabaya District. This study aims to determine the effect of the SQ3R strategy in improving reading learning outcomes of third-grade students at SD Negeri 1 Teko, Pringgabaya District. The research method used was an experiment with a one-group pretest-posttest design. The sample in this study was all 20 students of grade 3B of SD Negeri 1 Teko, Pringgabaya District. Data collection techniques were conducted using pretests and posttests in the form of multiple-choice tests. Data analysis in this study included normality testing using the Lilliefors test and hypothesis testing using the paired sample t-test. The results of the study showed that the pretest obtained the lowest score of 15 and the highest score of 85 with an average score of 51, while the posttest obtained the lowest score of 35 and the highest score of 95 with an average score of 65. Based on the results of the normality test, the pretest scores showed that Lhitung < Ltabel (0.0818 < 0.190), while the posttest scores showed that Lhitung < Ltabel (0.1560 < 0.190), indicating a normal distribution of the data. Furthermore, based on the results of the hypothesis test, the obtained thitung > ttabel (6,140 > 2.093), therefore the hypothesis